Exponential prototype structures for (2+1)-dimensional Boiti-Leon-Pempinelli systems in mathematical physics - Baskonus, Haci Mehmet; Bulut, Hasan (Taylor & Francis Ltd, 2016)
In this study, a new method called improved Bernoulli sub-equation function method has been proposed. This method is based on the Bernoulli sub-ODE method. After we mention the general properties of proposed method, we apply this algorithm to the (2+1)-dimensional Boiti-Leon-Pempinelli equation system. This gives us some new prototype solutions such as exponential and rational function solutions. Then, we have plotted two- and three-dimensional surfaces of analytical solutions. Finally, we have submitted a comprehensive conclusion.
Keywords: Traveling-Wave Solutions; Similarity Solutions; Soliton-Solutions; Symmetry; Equation